Yantar, a conserved arginine-rich protein is involved in Drosophila hemocyte development. - Sinenko, S.A.; Kim, E.K.; Wynn, R.; Manfruelli, P.; Ando, I.; Wharton, K.A.; Perrimon, N.; Mathey-Prevot, B. (Developmental Biology, 2004)
To identify novel factors involved in Drosophila hematopoiesis, we screened a collection of lethal recessive mutations that also affected normal hemocyte composition in larvae. We present the characterization of the gene yantar (ytr) for which we isolated null and hypomorphic mutations that were associated with severe defects in hemocyte differentiation and proliferation; ytr is predominantly expressed in the hematopoietic tissue during larval development and encodes an evolutionary conserved protein which is predominantly localized in the nucleus. The hematopoietic phenotype in ytr mutants is consistent with a defect or block in differentiation of precursor hemocytes: mutant larvae have enlarged lymph glands (LGs) and have an excess of circulating hemocytes. In addition, many cells exhibit both lamellocyte and crystal cell markers. Ytr function has been preserved in evolution as hematopoietic specific expression of the Drosophila or mouse Ytr proteins rescue the differentiation defects in mutant hemocytes.